Understanding pathways to recovery from alcohol use disorder in a Black community - Vose-O’Neal, Adam; Christmas, Shanesha; Alfaro, Karen A.; Dunigan, Robert; Leon, Alex P.; Hickman, Drew; Johnson, Andre; Kim, Meelee L.; Reif, Sharon (Frontiers in Public Health, 2025)
IntroductionBlack Americans suffer a range of health disparities rising from a long history of structural inequities and racism. Black individuals experience alcohol use disorder (AUD) at rates comparable to the general population, yet they suffer more negative consequences due to alcohol use such as illnesses, injuries, criminal-legal involvement, and social problems. The barriers they face challenge their ability to achieve recovery. However, the recovery needs of the Black population and the potential impact of racial disparities on pathways to recovery have not been examined.MethodsWe conducted semi-structured interviews with 37 participants in the Black-majority city of Detroit, Michigan, who identified as Black or African American and in recovery from AUD. Participants were 50 years old on average, 40% were women, and they reported being in recovery from alcohol for 8.4 years on average. We built upon a priori codes, using a framework analysis approach, to identify and code thematic domains related to recovery pathways.ResultsWe identified four overarching themes. (1) Delayed recovery initiation largely due to systemic challenges and a lack of knowledge about recovery, resulting in the belief that recovery was not possible. (2) Once initiating recovery, many reported getting stuck in chronic early recovery due to relapse cycles that regularly involved system and individual challenges coupled with inadequate support. (3) Use of blended recovery pathways, some common in the recovery literature (e.g., Alcoholics Anonymous), and some more prevalent in Black communities (e.g., religion/spirituality). (4) The facilitators of recovery vary by recovery stage; for example, receiving support was crucial in early recovery while providing support was important for sustained recovery.DiscussionParticipants’ stories emphasized the burdens experienced by this low-income Black community at personal, interpersonal, environmental and societal levels. They directly connected these burdens with the difficult mission of achieving and sustaining recovery from alcohol problems. Some challenges and recovery pathways were common in the broader population, and some, such as the impact of racism, were unique to this Black population. The results have meaningful implications for clinical treatment and recovery support improvements, to advance the recovery journeys of Black individuals with AUD.